Adoption of Seabank by Generation Z in Semarang City: An Extended Technology Acceptance Model (TAM) Approach - Afiat Sadida; Rani Raharjanti; Nurul Azmi (PT FORMOSA CENDEKIA GLOBAL, 2026)
The adoption of digital banking among Generation Z has become a strategic concern for financial institutions in Indonesia. This study aims to analyze the adoption of SeaBank by Generation Z in Semarang City by extending the Technology Acceptance Model (TAM) with the addition of perceived trust and subjective norm. The goal is to examine how perceived usefulness, perceived ease of use, perceived trust, and subjective norm impact attitudes toward using, and how these attitudes impact the intention to adopt SeaBank. Data were collected through an online questionnaire completed by 309 Generation Z respondents in Semarang City. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationships among the variables. The results show that perceived usefulness, perceived trust, and subjective norm have a significant impact on attitude toward using SeaBank. Perceived ease of use, however, does not have a statistically significant effect. Attitude toward using is found to significantly impact the intention to adopt seabank. This research contributes by adapting the Technology Acceptance Model in a digital banking context to Generation Z, who are highly familiar with technology and influenced by peer networks. The integration of trust and subjective norm provides additional explanatory power. The findings provide practical insights for digital banking providers to design strategies that enhance user trust, capitalize on social influence, and meet the expectations of younger users.